Access Control for MHN - Zhang, Kuan; Shen, Xuemin (Sherman) (Security and Privacy for Mobile Healthcare Networks, 2015)
In this chapter, we present access control schemes in MHNs. We mainly introduce several promising attribute based access control schemes, associated with some basic attribute-based encryption schemes such as CP-ABE, KP-ABE and multi-authority ABE.